Decision making framework for foreign direct investment: Analytic hierarchy process and weighted aggregated sum product assessment integrated approach. (22nd October 2021) - Gupta, Srikant; Jha, Babita; Singh, Rajesh Kumar
Abstract : Foreign direct investment (FDI) plays a paramount role in economic and social growth of every country. FDI acts as a source of external capital and helps in economic growth of the host country. Making decision for FDI during uncertain business environment is a challenge for all stakeholders. Therefore, in this study, we are proposing a decision making framework for FDI. Through literature review, we have identified the factors, on which FDI depends. A process‐based, multi‐criterion, integrated hierarchical approach for deciding about FDI, has been illustrated. In this study, five sectors are considered, that is, petroleum and natural resource, retailing and e‐commerce, healthcare, information technology, and road and highways for illustrating the proposed framework. It is observed that information technology sector has got top priority for FDI followed by retailing and e‐commerce and health care sector. Findings will help in taking appropriate decision by stakeholders for FDI. Ultimately it will also help in creating employment, economic growth, and welfare of society at large in the host country.